Role of stress‐inducible protein‐1 in recruitment of bone marrow derived cells into the ischemic brains. Issue 8 (8th July 2013) - Lee, Shin‐Da; Lai, Ted Weita; Lin, Shinn‐Zong; Lin, Chen‐Huan; Hsu, Yung‐Hsiang; Li, Chi‐Yuan; Wang, Hsiao‐Jung; Lee, Wei; Su, Ching‐Yuan; Yu, Yung‐Luen; Shyu, Woei‐Cherng
<x xml:space="preserve">Abstract</x> Stress‐inducible protein‐1 (STI‐1) is the proposed ligand for the cellular prion protein (PrPC), which is thought to facilitate recovery following stroke. Whether STI‐1 expression is affected by stroke and how its signalling facilitates recovery remain elusive. Brain slices from patients that died of ischemic stroke were collected for STI‐1 immunohistochemistry. These findings were compared to results from cell cultures, mice with or without the PrPC knockout, and rats. Based on these findings, molecular and pharmacological interventions were administered to investigate the underlying mechanisms and to test the possibility for therapy in experimental stroke models. STI‐1 was upregulated in the ischemic brains from humans and rodents. The increase in STI‐1 expression in vivo was not cell‐type specific, as it was found in neurons, glia and endothelial cells. Likewise, this increase in STI‐1 expression can be mimicked by sublethal hypoxia in primary cortical cultures (PCCs) in vitro, and appear to have resulted from the direct binding of the hypoxia inducible factor‐1α (HIF‐1α) to the STI‐1 promoter. Importantly, this STI‐1 signalling promoted bone marrow derived cells (BMDCs) proliferation and migration in vitro and recruitment to the ischemic brain in vivo, and augmenting its signalling facilitated neurological recovery in part by recruiting BMDCs to the ischemic brain. Our results thus identified a novel mechanism by which ischemic insults can trigger a self‐protective mechanism to facilitate recovery.